A Comparative Evaluation of Hypotheses to Explain the Black Hole Illusion. Issue 1 (2nd April 2020) - Robinson, F. Eric; Williams, Henry; Horning, Dain; Biggs, Adam T.
ABSTRACT: Objective : This study comparatively evaluated seven hypotheses to explain the Black Hole Illusion. Background : Several hypotheses have been proposed to explain the Black Hole Illusion (BHI), with differing predictions. The Constant Visual Angle hypothesis predicts that short runways should cause greater BHI. Meanwhile, several other hypotheses predict that longer runways should cause more severe BHI. In addition, there is debate whether lack of ground cues promotes BHI via autokinesis or by biasing pilots' perception of the runway. Method : Nineteen qualified pilots flew 27 simulated nighttime approaches in a fixed-base flight simulator. Participants flew under different combinations of runway length, starting distance from the runway, and starting altitude. We analyzed glideslope error, defined as a weighted sum of the error above or below a prescribed 3° glideslope, as well as RMSE around the approach path. Results : We found that pilots tended to demonstrate worse BHI effects during approaches to longer runways and when starting at low altitudes compared to high altitudes. Daylight and nighttime flights showed a similar variance around the glideslope. Conclusion : The constant visual angle hypothesis is not supported by our findings. We observed consistent glideslopes across starting locations and similar variance during day/night conditions, leading us to favor biased perception of the runway over autokinetic effects to explain the influence of contextual features on BHI.